Modelling non-alcoholic fatty liver disease (NAFLD) using human induced pluripotent stem cell (hiPSC)-derived hepatocytes - Lo, Peggy Cho Kiu (2022)
Non-alcoholic fatty liver disease (NAFLD) refers to a spectrum of disorders caused by accumulation of excess dietary lipids within the liver. NAFLD is the fastest growing chronic liver disease and without intervention can progress to liver cancer and liver failure. Poor prognosis and limited therapeutic options for patients is hindered by the absence of robust, human specific platforms for modelling NAFLD. We have access to a large three-generation family patient cohort that display a high rate of cirrhosis and hepatocellular carcinoma. The family have full range of manifestations of NAFLD and therefore represent a unique and ideal opportunity to investigate the pathogenesis of NAFLD. Whole exome sequencing of affected individuals has identified a rare, novel missense variant in microsomal triglyceride transfer protein (MTTP, 4q23). To address this need we have created an in vitro human model of NAFLD using hiPSCs derived from patients inherited NAFLD with MTTP-p.I564T single nucleotide variation. In this study, we have improved our differentiation protocol to differentiate hiPSCs into HLCs that are more similar to primary human hepatocytes than foetal hepatocytes. We demonstrated higher expression of cytochrome P450 enzymes as well as many genes involved in a broad range of metabolic processes including lipid biosynthesis and metabolism via transcriptomic analysis. We have then applied this more advanced platform to model NAFLD by inducing lipid accumulation in MTTPWT/WT and MTTPVAR/VAR hepatocytes using palmitic acid (PA). PA replicates a western high fat diet, we observed both control and MTTPVAR/VAR -HLCs demonstrate key features of hepatic steatosis such as intracellular accumulation of lipid droplets within the cytoplasmic space, as well as reduction of apolipoprotein B (apoB) secretion. MTTPVAR/VAR -HLCs when compared to healthy hepatocytes treated with PA show unique differences in their inflammatory and fibrotic gene expression profiles. We also detected significant reduction of eNOS phosphorylation in MTTPMUT/MUT-HLCs compared to healthy cell line, this may represent biomarkers for people with genetic predisposition to NAFLD, as well as novel interventions for familial-MTTP-p.I564T NAFLD patient. Finally, we also observe significant demand in metabolic profiles and mitochondrial functionality in MTTPVAR/VAR -HLCs overall, however, PA-treated condition in both wildtype and MTTPVAR/VAR-HLCs is associated with decreased mitochondrial maximal respiration. These findings may represent new mechanisms that drive the spectrum of clinical observations in the pathogenesis of NAFLD with MTTP-p.I564T genetic influence. Our study demonstrates the potential of hiPSC-HLCs to provide mechanistic insight and discovery of novel biomarkers and drug targets for NAFLD.